CO49 | The burden of cerebral small vessel disease in ITTP patients from acute phase to remission (Bleeding, Thrombosis and Vascular Biology)
Background: Immune-mediated thrombotic thrombocytopenic purpura (iTTP) is a life-threatening microangiopathy often characterized by acute neurological involvement during the acute phase followed by neurological complications during remission, due to microvascular damage. Cerebral small vessel disease (cSVD) is a condition affecting the brain small vessels leading to structural damage as assessed by magnetic resonance imaging (MRI). Age and hypertension are key risk factors for cSVD, which is often associated with stroke and dementia. To date, the prevalence of cSVD in iTTP patients remains unexplored. Aims: To assess the prevalence and progression of cSVD in iTTP patients.